PARATEXTUAL STRATEGIES IN ARABIC–INDONESIAN TRANSLATIONS OF AKIDAH-FIKIH TEXTS AT PUSTAKA YASIN - Matrokhim; Rumpoko Setyo Jatmiko; Aghnina Khoirun Nisa (Universitas Islam Negeri Raden Mas Said Surakarta, 2026)
The translation of Islamic texts requires careful negotiation between theological accuracy and readability. This study examines how that negotiation is realized in the Arabic-Indonesian translation practices of Pustaka Yasin. Using a descriptive qualitative approach with a single-case study design, this research analyzes translated Islamic texts supported by in-depth interviews with the main translator. The data focus on ambiguous terms, culture-bound expressions, and Islamic terminologies, as well as the use of paratextual elements such as footnotes, glosses, and interpolations. The findings show that Pustaka Yasin consistently balances doctrinal precision and reader accessibility through a combination of micro-level translation techniques, selective retention of Arabic terms, and systematic use of paratexts. This pattern indicates a managed foreignization strategy in which foreign elements are preserved while readability is maintained through guided explanation. The study contributes to Arabic-Indonesian translation studies by showing that paratext functions not merely as an editorial supplement but as a central mechanism for negotiating meaning in the translation of Islamic texts.